ANALISIS IMPLEMENTASI PROGRAM KELUARGA SEJAHTERA DI “KAMPUNG KB” DESA SUNGAI CAMBAI KECAMATAN MESUJI TIMUR KABUPATEN MESUJI TAHUN 2016 - Jamal Jamal; Sri Harti (e-JKPP, 2016)
The problems faced by several developing countries today are reducing the amount of poverty and increasing the welfare of the community by using various methods, both through improving economic infrastructure such as building roads, bridges, markets and other facilities, as well as building the degree and participation of the community through improving education and health and - government programs in terms of improving community welfare. Law Number 52 of 2009 concerning population development and a Prosperous Family is a solid foundation in controlling the population and the development of Indonesian families towards a balanced growing population and creating a happy and prosperous small family.The focus and location of this research is on the Implementation of the Prosperous Family Program in Kampung KB, Sungai Cambai District, which aims to examine the implementation of the Prosperous Family program as well as knowing and analyzing the factors that influence policy implementation. With a phenomenological approach, using qualitative methods, the researcher concludes that policy implementation has been good but there is still something that needs to be improved. Inhibiting factors for implementing a prosperous family program include resources, the degree of change desired, the position of policy makers, program implementers and the resulting resources. Supporting factors for the successful implementation of the Prosperous Family program, including information on socialization to the community, explanations that are quite clear and understandable from officers and positive interest from the community